Witness to History : the Life of John Wheeler-Bennett (Yale University Press, 2012)
Historian Sir John Wheeler-Bennett (1902-1975) was one of the twentieth century's most extraordinary political operators. Through an ability to make important connections, he became an authority on Germany in the inter-war years and knew all the German hierarchy, including Hitler and Hindenburg. He also was one of the last people to interview Trotsky, writing an important analysis of the Brest-Litovsk Treaty between Germany and the Soviet Union in 1917. As King George VI's official biographer, he met and interviewed all the major leaders in the post-war period, including Winston Churchill, Harry Truman, and members of the Royal Family; he also supervised young Jack Kennedy's master's thesis. With the first biography of Wheeler-Bennett Victoria Schofield has written a book tha will fascinate anyone interested in twentieth-century European history.&#160.